Mitochondrial ubiquitin ligase MARCH5 promotes TLR7 signaling by attenuating TANK action. - He-Xin Shi (Public Library of Science (PLoS), 2011)
The signaling of Toll-like receptors (TLRs) is the host's first line of defense against microbial invasion. The mitochondrion is emerging as a critical platform for antiviral signal transduction. The regulatory role of mitochondria for TLR signaling remains to be explored. Here, we show that the mitochondrial outer-membrane protein MARCH5 positively regulates TLR7 signaling. Ectopic expression or knockdown of MARCH5 enhances or impairs NF-κB-mediated gene expression, respectively. MARCH5 interacts specifically with TANK, and this interaction is enhanced by R837 stimulation. MARCH5 catalyzes the K63-linked poly-ubiquitination of TANK on its Lysines 229, 233, 280, 302 and 306, thus impairing the ability of TANK to inhibit TRAF6. Mislocalization of MARCH5 abolishes its action on TANK, revealing the critical role of mitochondria in modulating innate immunity. Arguably, this represents the first study linking mitochondria to TLR signaling.